2005
DOI: 10.3727/096504005776367898
|View full text |Cite
|
Sign up to set email alerts
|

Mutant IκBα Suppresses Hypoxia-Induced VEGF Expression Through Downregulation of HIF-1α and COX-2 in Human Glioma Cells

Abstract: Our previous study demonstrated that mutant IkappaBalpha (IkappaBalphaM) could inhibit glioma angiogenesis and tumorigenesis through the downregulation of vascular endothelial growth factor (VEGF) and IL-8. However, the pathways involved in VEGF expression are not well understood. Growing evidence indicates that hypoxia-inducible factor-1alpha (HIF-1alpha) and cyclooxygenases-2 (COX-2) play important roles in this progression. In this study, we first examined the expressions of hypoxia-induced genes in human g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…β-sitosterol attenuates insulin resistance by reducing insulin receptor substrate-1 (IRS-1) serine phosphorylation and activating downstream signaling molecules in rats [ 41 ]. Studies postulate that insulin stimulates HIF-1α [ 42 ], a nuclear transcription factor activated under hypoxic conditions, in a concentration-dependent manner [ 43 ]. Notably, it regulates a series of hypoxia signal pathways to enhance the expression of erythropoietin (EPO) and its receptor (erythropoietin receptor, EPOR) genes [ 44 ], thereby promoting the proliferation and differentiation of mammalian erythroid progenitor cells.…”
Section: Discussionmentioning
confidence: 99%
“…β-sitosterol attenuates insulin resistance by reducing insulin receptor substrate-1 (IRS-1) serine phosphorylation and activating downstream signaling molecules in rats [ 41 ]. Studies postulate that insulin stimulates HIF-1α [ 42 ], a nuclear transcription factor activated under hypoxic conditions, in a concentration-dependent manner [ 43 ]. Notably, it regulates a series of hypoxia signal pathways to enhance the expression of erythropoietin (EPO) and its receptor (erythropoietin receptor, EPOR) genes [ 44 ], thereby promoting the proliferation and differentiation of mammalian erythroid progenitor cells.…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that anti‐VEGF medication should be investigated for use in other types of radiation vasculopathy. This is interesting because VEGF seems to play a pivotal role in disruption of the integrity of the vessel wall during inflammation [83], and NF‐κB activates VEGF expression [83, 84] whereas inhibition of NF‐κB decreases levels of VEGF [85].…”
Section: Future Perspectives and Treatment Optionsmentioning
confidence: 99%
“…Our study found that SLC8A2 inhibited migration, invasion, and the tube formation of endothelial cells, as well as down-regulated the expression of VEGF189, VEGF165, and VEGF121. In addition, COX-2 and HIF-1α, tumor angiogenesis-related genes which can regulate VEGF expression ( Kimba et al, 2005 ), were also suppressed by SLC8A2 overexpression. These results suggested that SLC8A2 inhibited endothelium-dependent angiogenesis of glioblastoma.…”
Section: Discussionmentioning
confidence: 99%